A LITERATURE REVIEW ON THE ROLE OF YOGA IN SUPPORTING THE HEALTH OF PREGNANT WOMEN - Mayangsari, Nindya; Agustina, Nadia; Zaidan, Muhammad; Safrin, Safrin; Rustina, Rustina; Kristin Vandela, Zilva; Cindi Claudia, Maria (Proceeding of International Conference on Multidisciplinary Research, 2024)
Prenatal yoga has gained increasing popularity as an effective method for addressing various discomforts experienced by pregnant women. Yoga during pregnancy not only contributes to overall maternal health but also plays a significant role in enhancing well-being. Objective: This study aims to evaluate the impact of yoga practice on the health and well-being of pregnant women, focusing on literature published between 2020 and 2023. Methodology: The research involves a literature review, with sources drawn from various international journals accessed through online databases such as PubMed, JSTOR, Wiley Online Library, Taylor & Francis Online, and Sage Journals. The articles were accessed between June 1 and June 15, 2023. The search utilized keywords including "yoga" and "pregnancy". Article Selection: The initial search yielded 3,120 articles, which were then filtered based on inclusion and exclusion criteria. The inclusion criteria required English-language articles that studied the benefits of prenatal yoga for pregnant women and were available in full text. Articles that did not meet these criteria were excluded through a screening process that involved evaluating titles, abstracts, and full texts. Research Findings: Following the selection process, five articles were chosen for further analysis. The literature review revealed that prenatal yoga offers various benefits, including improved sleep quality, reduced anxiety and depression, enhanced cardiovascular function, decreased risk of pregnancy complications, and strengthened emotional bonds between mother and fetus. Conclusion: The review findings suggest that prenatal yoga provides significant physical and mental benefits for pregnant women. Therefore, it is recommended that this practice continues to be promoted as a key component of holistic prenatal care.